David Marcus Knight (1936–2018): An Appreciation. (3rd July 2019) - Brock, William H.
Abstract : The article is a biography of the historian of science, David M. Knight. It contains reminiscences of the author's relations with Knight while he was a postgraduate at Oxford and thereby conveys an impression of the state of history of science in Britain in the 1960s. It offers a conspectus of Knight's prolific literary activity and teaching career at the University of Durham. His love of chemistry and admiration for the work of Sir Humphry Davy is emphasised.